PATTERN OF BREAST CANCER: EXPERIENCE AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Shawana Asad; Sher Ali Khan; Fawad Ahmad Khan; Mir Jalal-ud-din; Ghazala Bhatti; Haider Kamran (Journal of Ayub Medical College Abbottabad, 2023)
Background: Breast cancer is the most common malignancy found in females all over the world and the second leading cause of cancer death in European countries. The purpose of this study was to find out the pattern of disease presentation in our region where a proper tumour registry system is lacking. Methods: This descriptive study was carried out in the Department of Surgery, Ayub Teaching Hospital Abbottabad, from July 2021 to June 2022. All female patients with biopsy-proven breast cancer were included in the study: benign lumps, refused to enrol, and those who were lost to follow-up were excluded. Results: A total of 87 patients with carcinoma breast were included: 92 % (n=80) had invasive ductal carcinoma. Axillary lymph nodes were involved in 88.5% (n=77), 75.8% of the tumours, (n=66), were Grade 2, 34.5% (n=30) were in the 40-49 years age group, and 30 % (n=27) of the disease was categorized as Stage III or IV. In 55 % (n=48), the tumour was on the right side and in 39% (n=34), the upper outer quadrant was involved. Most of the patients, 90.8% (n=79), were married and had used contraceptive measures. Only 19.5% of patients (n=17), had a history of nipple discharge and 56% (n=49) had a positive family history: 71% (n=62) had nipple retraction, and 54% (n=47), proved to be ER PR positive. Conclusion: Our patients presented late: axilla was commonly involved and a third had advanced disease. Screening and community awareness programs may help in early detection. Hormone use for contraception needs to be weighed carefully. Better data collection may help in designing screening and care programs.